STRATEGI GURU PPKN DALAM MENGANTISIPASI KEKERASAN PADA SISWA - Aryanti Dwi Untari; Elly Setiawati (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
This study aims to determine the strategies of teachers, especially teachers in anticipating violence against students.One of the phenomena that has caught the attention of the world of education today is violence that occurs in the school environment. Violence between students will certainly affect the learning conditions in the classroom. Students who experience physical and verbal abuse will certainly feel psychologically disturbed. Disturbed psychological conditions will also trigger disruption of the enthusiasm and interest of students in learning.The role of the teacher is very necessary to reduce even if it can eliminate the condition. Based on these problems, this study aims to: (1) determine the role of PPKn teachers in anticipating violence against students; (2). Knowing the obstacles of PPKn teachers in anticipating violence against students; (3). know what efforts are made by the PPKn teacher in anticipating violence against students. This research uses a descriptive method with a qualitative approach. Data collection techniques using observations, interviews and documentation conducted in the environment of SMK 17 Serang City. The research results obtained in the field show that the PPKn teacher's strategy in anticipating violence in children is to provide understanding related to norms about diversity, fostering character to care for each other, carrying out positive activities in the school environment such as extracurricular or social activities. others in the classroom environment and broadly in the school, and invites parents to control the activities of children in their environment.the strategy carried out by the teachers is done as an effort to prevent and deal with violence against students.